Pengaruh Pembatasan Sosial sebagai Upaya Menekan Penularan Covid-19 terhadap Kondisi Kesehatan Mental Remaja: Literature Review - Dita Riski Khasanah; Hennanda Annastya Annisa Indarko; Ida Rosilawati; Dwi Sarwani Sri Rejeki (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: At the end of April 2021, the occurrence of Covid-19 in Indonesia has reached 1.63 million cases and 44,172 deaths. The social restriction policy is an effort for the government to suppress the rate of transmission of Covid-19, although on the other hand, this policy also raises fear, anxiety, and worry for the community, including teenagers. The emotional development and behaviour of adolescents towards adulthood require social space, but are constrained by social restrictions. Objective: to determine the effect of social restrictions on adolescent mental health. Methods: This study uses a literature review method from 2019 to 2021 obtained from the Google Scholar, PubMed, and Science Direct databases using the keywords social restrictions, youth, mental health disorders, Youth and Children, Covid-19, Impact, and mental health. . The criteria for the selected articles were articles published in 2019-2021 nationally and internationally related to literature review research. Results: the impact of social restrictions on the mental health of adolescents is quite varied. The existence of limitations in socializing, boredom and the many tasks assigned to adolescents are the main factors for adolescents experiencing mental disorders such as stress, depression, and anxiety. Conclusion: social restrictions indirectly have an impact on the mental health of adolescents and even trigger mental health disorders in adolescents.